Design and Fabrication of a Prototype Automated Instant Noodle Vending Machine - Biglete, Emmanuelle R.; Landicho Jr., Manolito M.; Quicho, Florence Rei V.; Sauli, Zaliman (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The project aims to help people especially those who are working in call centres to enjoy eating noodles easily and quickly during their short breaks. The unique feature of this instant noodle vending machine is that it eliminates the use of plastic or paper cups during dispensing. Instead, cooked noodle mix is directly dispensed into the mug provided by the user. The working prototype is flexible to dispense crushed noodles, four different flavours to choose from, and hot water. The dispensing process is sequential which starts from the detection of the cup, crushed noodles dispensing, seasoning dispensing based on the desired flavour, and lastly, the water injection. The researchers were able to design and fabricate the machine based on set standards with an acceptable percent error which are within the tolerance limits. The working prototype was fabricated, and statistical results showed an acceptable range of values.